Do Remittances Enhance Financial Development in Transitional Markets? - Kunofiwa Tsaurai; Patience Hlupo (Comparative Economic Research. Central and Eastern Europe, 2019)
The paper explored (1) the impact of remittances on financial development and (2) whether the interaction between remittances and human capital development had an influence on financial development in transitional economies using the dynamic GMM approach, with data ranging from 1996 to 2014. Remittances were found to have had a non-significant positive influence on financial development in transitional economies when stock market turnover, stock market value traded, domestic credit to the private sector by banks, and public bond sector development were used as measures of financial development. When stock market capitalisation, domestic credit to the private sector by financial sector, and private bond sector development were used as measures of financial development, remittances had a non-significance negative effect on financial development. Using all other measures of financial development except stock market capitalisation (which produced a negative sign), the interaction between remittances and human capital development had an insignificant positive influence on financial development. Transitional economies are therefore urged to avoid over-relying on remittance inflow and human capital development as sources of financial development.
Keywords: F24; G15; P02; 330; remittances; financial development; transitional economies